2003
DOI: 10.1016/s0378-1097(03)00399-9
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular polymeric substances responsible for bacterial adhesion onto solid surface

Abstract: The influence of extracellular polymeric substances (EPS) on bacterial cell adhesion onto solid surfaces was investigated using 27 heterotrophic bacterial strains isolated from a wastewater treatment reactor. Cell adhesion onto glass beads was carried out by the packed-bed method and the results were discussed in terms of the amount of each EPS component produced and cell surface characteristics such as zeta potential and hydrophobicity. Protein and polysaccharides accounted for 75^89% of the EPS composition, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
222
1
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 470 publications
(246 citation statements)
references
References 28 publications
16
222
1
3
Order By: Relevance
“…However, NH 4 þ -N was removed to a greater extent by the CAUF cake layer after a long operation time (as indicated in Stage 1), and this could be attributed to the development of a higher concentration of microorganisms with increasing run time. Tsuneda et al [58] reported that sludge adhesion was enhanced by polymeric interactions when the bound EPS content increased. Sludge with abundant bound EPS tends to adhere to the membrane surface and form a stable structure, which could prevent the cake layer from being washed away.…”
Section: Discussionmentioning
confidence: 99%
“…However, NH 4 þ -N was removed to a greater extent by the CAUF cake layer after a long operation time (as indicated in Stage 1), and this could be attributed to the development of a higher concentration of microorganisms with increasing run time. Tsuneda et al [58] reported that sludge adhesion was enhanced by polymeric interactions when the bound EPS content increased. Sludge with abundant bound EPS tends to adhere to the membrane surface and form a stable structure, which could prevent the cake layer from being washed away.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, our observations support the conclusion that the psl cluster encodes gene products that are required for mediating cell-surface and cell-cell interactions. Initial attachment requires that a repulsion barrier between a negatively charged bacterial cell and a surface must be overcome (55,56). Different exopolysaccharides, such as those from Vibrio sp., acidic polysaccharides of marine pseudomonads, and Staphylococcus epidermidis PIA and PS/A clearly promote adherence (6,18,32,35,65).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, studies of EPS extracted from activated sludges show a majority of proteins (McSwain et al 2005;Ge et al 2007;Park and Novak 2007). In smaller quantities, humic-like substances (Frølund et al 1995), uronic acids (Tsuneda et al 2003), and nucleic acids (Zhang et al 1999) are also EPS constituents. Nucleic acids are released after cell lysis.…”
Section: Introductionmentioning
confidence: 99%